Phytochemical Constituents and Biological Activity of Curcuma Aeruginosa Roxb., C.Ochrorhiza Val. and Andrographis Asculata Nees - Md. Saad, Suhaila (2006)

(untitled)
Tropical plants have been acknowledged to be the source of variety of forest products that could be exploited as potential pharmaceutical, natural insecticides, oils, foods and other industrial goods. Out of these only a small proportion has been systematically investigated. This research has been carried out to investigate the chemical constituents and bioactivities of Curcuma aeruginosa, Curcuma ochrorhiza and Andrographis asculata. In this present study, the rhizomes of Curcuma aeruginosa and Curcuma ochrorhiza and also the leaves of Andrographis asculata were investigated and have resulted in the isolation of eight pure compounds and three mixtures. The structures of the pure compounds were elucidated by using spectroscopic experiments namely NMR, MS and IR, while the constituents of the mixtures were identified using GC-MS technique. Detailed chemical studies on Curcuma aeruginosa have yielded three sesquiterpenes, curcumenol (10), zedoarol (6) and isocurcumenol (43) and phytosterol mixtures containing stigmasterol (52) and α-sitosterol (53). Isocurcumenol (43) was isolated for the first time from this plant species, whereas the occurrences of other compounds have been reported previously. Meanwhile investigations on Curcuma ochrorhiza have afforded three sesquiterpenes, zederone (13), zerumbone (46) and furanodienone (2), two triterpenes namely stigmasterol (52) and α-sitosterol (53) and mixtures of long chain compounds comprising of tricosanoic acid (54) and ester of tetradecanoic acid (55). Zerumbone (46) and furanodienone (2) were isolated for the first time from this species. Studies on Andrographis asculata have yielded α-sitosterol (53) as the major constituent and mixtures of docosanoic acid (56), hexadecanoic acid (57), tetradecanoic acid (dodecyl ester) (58) and hexacosanoic acid (59). Cytotoxic tests were performed using HL-60 cell lines and CEM-SS cell lines. The crude chloroform extract of Curcuma aeruginosa and crude hexane extract of Curcuma ochrorhiza were consider being active against CEM-SS cell lines with IC50 values 6 μg/mL. Meanwhile, pure compounds isolated from Curcuma ochrorhiza, zederone (13) and zerumbone (46) were found to be very active against CEM-SS and HL-60 cell lines. As for antimicrobial test, crude chloroform extract of Curcuma aeruginosa were mildly active against four bacteria used in the test, while crude methanol extract of Andrographis asculata exhibited mild activity against Bacillus substillis. In addition, two isolated compounds isocurcumenol (10) and zerumbone (46) were found to be moderately active against some of the microbes. The antioxidant activity of all extracts from Curcuma aeruginosa were close to or lower than quarcetin, and this suggest that the crude extract posses antioxidant activity. The results also showed the same pattern with all crude extracts of Curcuma ochrorhiza. Two pure compounds from Curcuma aeruginosa were also subjected to the screening of antioxidant tests and the results showed curcumenol (10) and isocurcumenol (43) did posses antioxidant activity. Meanwhile, the crude hexane and CHCl3 extract of Andrographis asculata also showed antioxidant activity, while the crude methanol extract was not active.